Incentive Policy for Battery Energy Storage Systems Based on Economic Evaluation Considering Flexibility and Reliability Benefits - Cai, Shengxia; Li, Ying (Frontiers in Energy Research, 2021)
The efficient application of battery energy storage system (BESS) technology can effectively alleviate the uncertainty and volatility caused by distributed generations (DGs) and loads, and reduce their adverse effects on power grid, and delay equipment capacity upgrades, improve equipment utilization, save costs, and increase the system hosting capacity for renewable energy. However, the application of BESS is restricted by its high cost and limited policy support. Therefore, it is necessary to carry out the economic evaluation of BESS considering flexibility and reliability improvement, and incentive policy research to promote its deployment. The novelty of this study on BESS lies in the following four aspects: 1) A reliability-benefit model for BESS considering the value of electricity in the national economy is proposed. 2)A flexibility improvement benefit calculation model of BESS is built with the definition of flexibility indexes of distribution network related to BESS considering the capacity and charge and discharge constraints. 3) A reliability improvement benefit calculation model of BESS is built, and the detailed calculation flow of economic evaluation model for BESS users considering net present value (NPV) index and dynamic payback period (DPP) index is proposed. 4) The impact analysis of different prices and incentive policies on BESS business models is carried out, and then incentive policy based on flexibility and reliability improvement is presented. The results of the IEEE 33-node test system show that the flexibility and reliability improvement can effectively reflect the benefit and cost of BESS, and the incentive policies can help to promote the development of BESS technology.